2019
DOI: 10.1021/acs.cgd.9b01209
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Series of Sulfamethazine Multicomponent Crystals with Various Benzoic Acids

Abstract: Nine multicomponent crystals consisting of sulfamethazine (sz) with benzoic acid and its derivatives were synthesized and characterized. Eight of the nine multicomponent crystals are cocrystals, while one is a molecular salt. The coformers used to form multicomponent crystals with sz include 2-chloro-4-nitrobenzoic acid (2c4n), 2-chloro-5-nitrobenzoic acid (2c5n), salicylic acid (2hba), 3-hydroxybenzoic acid (3hba), 4-hydroxybenzoic acid (4hba), 4-bromobenzoic acid (4Brba), benzoic acid (ba), cinnamic acid (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Crystalline LH showed its melting point around 260 °C, followed by a small thermal degradation peak (Figure a), which was the same as with our previous report . We found the fusion endotherms of pHCA and CA were 222.8 and 134.3 °C, respectively (Figure b,c), which were consistent with the reported results. , Moreover, it was observed that the physical mixtures of LH and CA exhibited two endothermic peaks, similar to their melting points (Figure S2a–c). However, the physical mixtures of LH and pHCA showed only one melting endotherm in the temperature range of 174–177 °C (Figure S2d–f), probably suggesting that a low eutectic mixture was formed between LH and pHCA.…”
Section: Resultssupporting
confidence: 91%
“…Crystalline LH showed its melting point around 260 °C, followed by a small thermal degradation peak (Figure a), which was the same as with our previous report . We found the fusion endotherms of pHCA and CA were 222.8 and 134.3 °C, respectively (Figure b,c), which were consistent with the reported results. , Moreover, it was observed that the physical mixtures of LH and CA exhibited two endothermic peaks, similar to their melting points (Figure S2a–c). However, the physical mixtures of LH and pHCA showed only one melting endotherm in the temperature range of 174–177 °C (Figure S2d–f), probably suggesting that a low eutectic mixture was formed between LH and pHCA.…”
Section: Resultssupporting
confidence: 91%
“…The first one is sulfamethazine. The amidine tautomer, imidine tautomer, anion, and cation have been observed in the structures of sulfamethazine and its crystalline complexes. The other three APIs are piroxicam, meloxicam, and enrofloxacin, all of which showed the existence of neutral and zwitterionic molecular forms, as well as cationic and anionic states in reported structures. For sulfamethazine, piroxicam, and enrofloxacin, the proton tautomeric sites are consistent with the protonation/deprotonation sites. Meloxicam shows a little difference.…”
mentioning
confidence: 78%
“…8,9 The solidstate separation of the tautomers of some tautomeric molecules has been achieved using this method. [10][11][12][13][14][15] New strategies should be developed to realize the solid-state separation of the tautomers of more tautomeric molecules. We proposed that the solid-state separation of the tautomers of the same molecules can be realized by doping the tautomeric molecules in an existing tautomeric polymorph or amorphous phase of their similar molecules with a definite tautomeric form which would induce them to dope with a certain tautomeric form.…”
Section: Introductionmentioning
confidence: 99%